Public Satisfaction Based on the Quality of Online Mail Services in Mantingan Tahunan Jepara Islamic Perspective - Purwati Purwati; Triana Hasty Kusuma; Sofia Ulfah; Indra Lina Putra; Muhammad Ali Subkhan (Jurnal Ilmiah Ekonomi Islam, 2023)
This study aims to determine the effect of online mail service quality on public satisfaction in Mantingan Village and to determine the sub-variables of service quality that have the most influence on Public satisfaction. The sample taken is 100 people from this entire population 11.746 people with the Slovin formula. The results showed that service quality has a positive influence on Public satisfaction 0,757 with a significant level of 95%. That means that 75,7 % of people's satisfaction receive online mail services Mantingan Village can be influenced by several sub-variables such as tangible, empathy, reliability, responsiveness, and assurance , the remaining 24,3 % is influenced by other independent variables that have not been shown in this study, which have the most influence in satisfying the people who receive online mail services. Mantingan village is empathy with a regression coefficient of 0.866.